Relationship of Birth Weight and Birth Length with the Incidence of Stunting - Putri, Yulia Rahmawati Wibowo; Mulyani, Sri; Wiboworini, Budiyanti (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Stunting is a malnutrition problem that is often found in children under five. Stunting can cause a decrease in endurance, intelligence and can cause growth disorders. Objective: This study aims to determine the relationship between the history of birth weight and birth length of children aged 6-24 months with the incidence of stunting at Purwosari Health Center, Surakarta. Method: Analytical observational research with a cross sectional approach using secondary data sourced from nutritional status data of children aged 6-24 months at Purwosari Health Center, Surakarta. Results: The results of the analysis of the relationship between birth weight and the incidence of stunting obtained a p-value = 0.025, the relationship between birth length and the incidence of stunting obtained a p-value = 0.001. Conclusions: There is a significant relationship between birth weight and birth length with the incidence of stunting.